Development of large intestine of buffalo - SINGH, OPINDER; ROY, K S; SETHI, R S; KUMAR, ANOOP (The Indian Journal of Animal Sciences, 2012)
The present study was conducted on large intestine of 36 buffalo fetuses ranging from 4 cm to 92 cm curved crown rump length (CVRL). The mucosal projections appeared in large intestine during early stages of development whereas villi were first observed at 19.5 cm CVRL (119 days) in rectum. The degeneration of villi started at 39.0 cm CVRL (161 days) in rectum and villi disappeared at 88.0 cm CVRL (272 days) in all segments of large intestine. The epithelium was undifferentiated stratified type during early development and started transforming to simple columnar at 44.5 cm CVRL (174 days).The goblet cells appeared in rectum at 31.0 cm CVRL (144 days) and in caecum and colon at 39.0 cm (161 days). The intestinal glands were fully differentiated at 55.0 cm CVRL (198 days). The lamina muscularis mucosae appeared in all segments of large intestine at 60.2 cm CVRL (212 days). Tunica muscularis comprised of inner circular and outer longitudinal layer at 14.7 cm CVRL (95 days). Tunica serosa was well organized at 19.5 cm CVRL (119 days).